The role of FOXOs and autophagy in cancer and metastasis—Implications in therapeutic development. Issue 6 (31st May 2020) - Farhan, Mohd; Silva, Marta; Li, Shuai; Yan, Fengxia; Fang, Jiankang; Peng, Tangming; Hu, Jim; Tsao, Ming‐Sound; Little, Peter; Zheng, Wenhua
Abstract: Autophagy is a highly conserved intracellular degradation process that plays a crucial role in cell survival and stress reactions as well as in cancer development and metastasis. Autophagy process involves several steps including sequestration, fusion of autophagosomes with lysosomes and degradation. Forkhead box O (FOXO) transcription factors regulate the expression of genes involved in cellular metabolic activity and signaling pathways of cancer growth and metastasis. Recent evidence suggests that FOXO proteins are also involved in autophagy regulation. The relationship among FOXOs, autophagy, and cancer has been drawing attention of many who work in the field. This study summarizes the role of FOXO proteins and autophagy in cancer growth and metastasis and analyzes their potential roles in cancer disease management.